Understanding environmental content and sentiments in the pre- and post-COVID-19 era using a netnographic approach - Olivos Salas, Brenda; Papiż, Barbara; Micek, Grzegorz; Grodzińska-Jurczak, Małgorzata (Society Register, 2025)
The success of transitions towards sustainability depends on broad social support. This study examines how extreme events—in this case the COVID-19 pandemic—can influence public engagement with environmental issues. The pandemic affected many sectors, including the plastics industry, which experienced an increase in both production and consumption, particularly of single-use plastics (SUPs). By analysing social media activity before and after the COVID-19 outbreak using a netnographic methodology, we demonstrate how Twitter users responded to the dilemma posed by the rise in SUPs. We analysed five European Twitter accounts representing various stakeholders involved in the SUP sector. Data collected between 2017 and 2022 show a marked decline in the number of Tweets related to SUPs. Correlations between the COVID-19 Stringency Index and the numbers of Tweets, likes per Tweet, replies per Tweet and retweets per Tweet indicate that the pandemic significantly influenced the social media discourse surrounding SUPs. A qualitative assessment of Tweet content, authorship and tonality provides additional insights into these dynamics. Furthermore, the study confirms that acquiring qualitative data through Twitter—a social media platform—is feasible in the context of extreme events such as pandemics. Further research is required to generalise the role of online communication in shaping environmental discourse over specific time periods.